Complete Response of a Patient With a Mismatch Repair Deficient Aggressive Pituitary Adenoma to Immune Checkpoint Inhibitor Therapy: A Case Report. Issue 2 (13th August 2022) - Shah, Sanjit; Manzoor, Saima; Rothman, Yehudit; Hagen, Matthew; Pater, Luke; Golnik, Karl; Mahammedi, Abdelkader; Lin, Andrew L.; Bhabhra, Ruchi; Forbes, Jonathan A.; Sengupta, Soma
Abstract : BACKGROUND AND IMPORTANCE: Aggressive pituitary adenomas (APAs) are pituitary tumors that are refractory to standard treatments and carry a poor prognosis. Current treatment guidelines are not standardized but combine surgical resection, radiation therapy, and chemotherapy. Temozolomide is the only chemotherapeutic agent with documented effectiveness and is recommended for APA in European Society of Endocrinology clinical guidelines. CLINICAL PRESENTATION: A 57-year-old man presented with visual deterioration and bitemporal hemianopsia. MRI of the brain demonstrated a sellar mass suspected to be pituitary macroadenoma with displacement of the stalk and optic nerve impingement. The patient underwent stereotactic endoscopic transsphenoidal resection of the mass. Postoperative MRI demonstrated gross total resection. Pathology revealed a sparsely granulated corticotroph adenoma with malignant transformation. Immunohistochemistry showed loss of expression of MLH1 and PMS2 in the tumor cells. Proton therapy was recommended given an elevated Ki67 index and p53 positivity. Before radiotherapy, there was no radiographic evidence of residual tumor. Temozolomide therapy was initiated after surveillance MRI showed recurrence at 16 months postoperatively. However, MRI demonstrated marked progression after 3 cycles. Next-generation sequencing using the MSK-IMPACT platform identified somatic mutations in MLH1 Y548lfs*9 and TP53 R337C . Immunotherapy with ipilimumab/nivolumab was initiated, and MRI demonstrated no residual tumor burden 34 months postoperatively. CONCLUSION: APA is a tumor with frequent recurrence and a short median expected length of survival. Here, we demonstrate the utility of immunotherapy in a single case report of APA, with complete resolution of recurrent APA and improved survival compared with life expectancy.